Structural and dynamical determinants of a β-sheet-enriched intermediate involved in amyloid fibrillar assembly of human prion protein. Issue 35 (23rd August 2022) - Russo, Luigi; Salzano, Giulia; Corvino, Andrea; Bistaffa, Edoardo; Moda, Fabio; Celauro, Luigi; D'Abrosca, Gianluca; Isernia, Carla; Milardi, Danilo; Giachin, Gabriele; Malgieri, Gaetano; Legname, Giuseppe; et al.
Abstract : The N-ter domain in HuPrP regulates the folding mechanism by tuning the long-range μs–ms dynamics. Removal of the N-ter domain triggers the formation of a stable β-enriched intermediate state inducing amyloid aggregates with HuPrP Sc seeding activity. Abstract : The conformational conversion of the cellular prion protein (PrP C ) into a misfolded, aggregated and infectious scrapie isoform is associated with prion disease pathology and neurodegeneration. Despite the significant number of experimental and theoretical studies the molecular mechanism regulating this structural transition is still poorly understood. Here, via Nuclear Magnetic Resonance (NMR) methodologies we investigate at the atomic level the mechanism of the human HuPrP(90–231) thermal unfolding and characterize the conformational equilibrium between its native structure and a β-enriched intermediate state, named β-PrPI. By comparing the folding mechanisms of metal-free and Cu 2+ -bound HuPrP(23–231) and HuPrP(90–231) we show that the coupling between the N- and C-terminal domains, through transient electrostatic interactions, is the key molecular process in tuning long-range correlated μs–ms dynamics that in turn modulate the folding process. Moreover, via thioflavin T (ThT)-fluorescence fibrillization assays we show that β-PrPI is involved in the initial stages of PrP fibrillation, overall providing a clear molecular description of the initial phases of prion misfolding. Finally, we show by using Real-Time Quaking-Induced Conversion (RT-QuIC) that the β-PrPI acts as a seed for the formation of amyloid aggregates with a seeding activity comparable to that of human infectious prions.